Serial composition and atonality: An instroduction to the music of Schoenberg, Berg and Webern - Perle, George (Berkeley University of California Press, 1991)
Widely recognized as the definitive work in its field ever since its original publication in 1962, Serial Composition and Atonality remains an unsurpassed introduction to the technical features of what is probably the most revolutionary body of work since the beginnings of polyphony. In the analysis of specific compositions there is first and last of all a concern with the musical surface--an attempt to trace connections and distinctions there before offering any deeper-level constructions, and to offer none where their effects are not obvious on more immediate levels of musical experience. In this sixth edition of the book, George Perle employs the new and more consistent terminology for the identification of transpositional levels of twelve-tone sets that he first proposed in Twelve-Tone Tonality (1977).